2012
DOI: 10.1063/1.4769043
|View full text |Cite
|
Sign up to set email alerts
|

Photocathode device using diamondoid and cesium bromide films

Abstract: A photocathode structure is presented that shows promise for use in high brightness electron sources. The structure consists of a metal substrate, a monolayer of a diamondoid derivative, and a thin film of cesium bromide. Diamondoid monolayers reduce the energy spread of electron emitters, while cesium bromide increases the yield and stability of cathodes. We demonstrate that the combined structure retains these properties, producing an emitter with lower energy spread than the corresponding cesium bromide emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Another approach to solving the long-term stability issue of the diamondoid monolayer, as reported by Clay et al [147], is by providing a protective overlayer. In their study, cesium bromide (CsBr), which is an electron transparent compound, was deposited onto the monolayer of TA 121 -6-thiol on Au through vapor deposition.…”
Section: Diamondoid As Electron Emittersmentioning
confidence: 99%
“…Another approach to solving the long-term stability issue of the diamondoid monolayer, as reported by Clay et al [147], is by providing a protective overlayer. In their study, cesium bromide (CsBr), which is an electron transparent compound, was deposited onto the monolayer of TA 121 -6-thiol on Au through vapor deposition.…”
Section: Diamondoid As Electron Emittersmentioning
confidence: 99%
“…Higher diamondoids have a potential as building blocks for nanoelectronic devices. It was shown that tetramantane thiol form well-ordered self-assembled monolayers (SAMs) on gold surface and material [2][3][4][5][6] thus obtained display monochromatic electron emission with low-kinetic energy threshold [3]. Besides, diamondoids and their derivatives serve as a model for hydrogen terminated diamond nanoparticles [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the diamondoid only exists as hexamantanes and pentamantanes (particle size of 0.6-0.75 nm) for the rod-shaped isomer in limited quantities from oil. Therefore, diamondoids with the desired size larger than 1 nm, in order to explore applications in nanoelectronics [1][2][3][4], for which the present of quantum limitation effects are theoretically presaged, remains problematic at the present time. This can be solved by a coupling reaction using lower diamondoids with various spacers.…”
Section: Introductionmentioning
confidence: 99%